Il "tempo ultimo": strutture della temporalità nell'opera di Italo Svevo - Stellardi, G (Universidad Complutense Madrid, 2012)
This essay follows the development of the theme of time in Italo Svevo’s narrative work, through the three novels and the short texts of the last period. The Triestine writer shows an ever increasing awareness, not only of the centrality of time in the constitution of specifically human horizons of comprehension of reality, but also a more and more precise notion of the inextricable connection between temporality and literary writing. The deployment of conceptual categories linked to various dimensions of time highlights the interest and enduring validity of Svevo’s points of view concerning the nexus life-literature.